Fabrication of highly ordered nanohoneycomb (ZnO/Pt) arrays. (2014) - Lee, Chao-Te; Chiang, Donyau; Chiu, P.K.; Cho, Wen-Hao; Ou, Sin-Liang
The double nanohoneycombs (ZnO/Pt) on glass and Si substrates were fabricated by the two-step process of nanosphere lithography (NSL). The working parameters of the fabrication processes on nanohoneycomb performances were analysed and the factors affecting the size of nanohoneycombs, such as controlling nanosphere size, lift-off nanosphere and the second NSL process, were elucidated. In the first-step NSL process, an ordered single layer of polystyrene (PS) nanospheres with an average diameter of 600 nm was spin-coated on the substrates. Then, the PS nanospheres were modified and reduced by oxygen plasma and performed as deposition masks. By ZnO film deposition and lift-off processes sequentially, we fabricated ordered periodic nanohoneycomb (ZnO) arrays. After repeating the second-step NSL process and Pt film deposition on the ZnO arrays, we fabricated an ordered structure with periodic double nanohoneycomb (ZnO/Pt) arrays. This technique for forming double nanohoneycombs, especially with desired period, is expected to be a candidate for manufacturing wide nanostructures used in different fields, such as photonic crystals, optoelectronic devices, sensors, data storage and fuel cells.